2012
DOI: 10.1101/cshperspect.a008342
|View full text |Cite
|
Sign up to set email alerts
|

Building Muscle: Molecular Regulation of Myogenesis

Abstract: SUMMARYThe genesis of skeletal muscle during embryonic development and postnatal life serves as a paradigm for stem and progenitor cell maintenance, lineage specification, and terminal differentiation. An elaborate interplay of extrinsic and intrinsic regulatory mechanisms controls myogenesis at all stages of development. Many aspects of adult myogenesis resemble or reiterate embryonic morphogenetic episodes, and related signaling mechanisms control the genetic networks that determine cell fate during these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
922
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 918 publications
(957 citation statements)
references
References 185 publications
22
922
1
12
Order By: Relevance
“…52 As discussed earlier, MyoD acts upstream of myogenin and transcriptionally activates myogenin. 8,9,13,14 We anticipated that p53 would repress endogenous myogenin transcription activated by ectopic MyoD and would not repress ectopic myogenin driven by a constitutive promoter. This experimental design allowed us to characterize myogenin function in either a p53-dependent or p53-independent manner.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…52 As discussed earlier, MyoD acts upstream of myogenin and transcriptionally activates myogenin. 8,9,13,14 We anticipated that p53 would repress endogenous myogenin transcription activated by ectopic MyoD and would not repress ectopic myogenin driven by a constitutive promoter. This experimental design allowed us to characterize myogenin function in either a p53-dependent or p53-independent manner.…”
Section: Resultsmentioning
confidence: 99%
“…p53 25,26,53,54 MyoD determines the myogenic lineage and acts upstream of p21 and myogenin. 8,9,13,56 Under normal conditions, expression of both p21 and myogenin is critical to establish the state of irreversible cell cycle arrest and terminal differentiation. 11,16,40 In contrast to the cell cycle arrest that promotes terminal differentiation under non-stressed conditions, it is known that cell cycle arrest induced by DNA damage is associated with decreased myogenic differentiation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent molecular studies have suggested that aRMS represents an arrested stage of development of undifferentiated myoblasts. The cause of the arrested stage of development could be related to the PAX-FKHR mutation and fusion, which leads to increased levels of MyoD1 and myogenin, resulting in cell proliferation and myogenic differentiation, respectively (Bentzinger et al, 2012;Caserto, 2013).…”
mentioning
confidence: 99%